USE OF DIGITAL TECHNOLOGIES IN THE FORMATION OF ACCOUNTING AND ANALYTICAL INFORMATION BY ENTERPRISE MANAGERS (Economic journal of Lesya Ukrainka Volyn National University, 2019)
Due to the dynamic development of accounting, there is a process of active integration of traditional methods of accounting, analysis, control and audit with managerial techniques in a single analytical and accounting system of data acquisition and processing. The importance of accounting and analytical information in making science-based management decisions in a fast-changing external environment, uncertainty in the behavior of economic entities of the market significantly increases and depends on the quality of accounting and reporting space, that is provided by using digital technologies. The integrated accounting and analytical management system of financial and economic activities, which has a «synergistic effect», will make it possible to manage business successfully on a full scale, form a general data base, which provides the process of decision-making.
Keywords: principles of accounting and analysis system, «synergistic effect», a systematicapproach, function, elements of accounting and analysis system: accounting, controland auditing, management decisions